2013
DOI: 10.1002/lary.24359
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet and anticoagulation therapy in microlaryngeal surgery

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 30 publications
3
20
0
Order By: Relevance
“…Francis et al performed a retrospective review regarding the safety of antiplatelet therapy in patients undergoing operative microlaryngeal surgery under general anesthesia and showed that there was no difference in the incidence of bleeding complications based on antiplatelet status. 22 Another study by Fritz et al showed that continuing these treatments during in-office laryngeal procedures did not increase the risk of complications. 23 The decision to hold antithrombotic therapy is dependent on the risk of perioperative bleeding if the antithrombotic therapy were to be continued, versus the thromboembolic risk if the therapy were interrupted or discontinued.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Francis et al performed a retrospective review regarding the safety of antiplatelet therapy in patients undergoing operative microlaryngeal surgery under general anesthesia and showed that there was no difference in the incidence of bleeding complications based on antiplatelet status. 22 Another study by Fritz et al showed that continuing these treatments during in-office laryngeal procedures did not increase the risk of complications. 23 The decision to hold antithrombotic therapy is dependent on the risk of perioperative bleeding if the antithrombotic therapy were to be continued, versus the thromboembolic risk if the therapy were interrupted or discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to results of previous studies regarding laryngeal surgery. Francis et al performed a retrospective review regarding the safety of antiplatelet therapy in patients undergoing operative microlaryngeal surgery under general anesthesia and showed that there was no difference in the incidence of bleeding complications based on antiplatelet status . Another study by Fritz et al showed that continuing these treatments during in‐office laryngeal procedures did not increase the risk of complications …”
Section: Discussionmentioning
confidence: 99%
“…no increased risk of bleeding in patients on antithrombotics. 25 Subsequent studies by Fritz et al and Dang et al had similar findings in the office setting and at the bedside, respectively, but the smaller size of these studies prevented them from drawing formal conclusions. 7,26 The present study sought to validate the findings of those before which would require about 5000 patients per group.…”
Section: Introductionmentioning
confidence: 94%
“…Several studies support the safe continuation of aspirin therapy during various otolaryngologic and other surgical procedures anatomically related to the head and neck, including cataract surgery, 29 vitreoretinal surgery, 30 dental osteotomy, 31 cutaneous surgery, 32,33 in-office laryngologic procedures, 34 and microlaryngeal surgery. 35 Nevertheless, scarce evidence and Abbreviations: BMI, body mass index (calculated as the weight in kilograms divided by height in meters squared); EBL, estimated blood loss; NA, not applicable; RLN, recurrent laryngeal nerve; SBL, substantial blood loss (EBL >10 mL); TSH, thyroid-stimulating hormone. a Effect size calculated using raw group differences, including comparison of means and comparison of proportions where appropriate.…”
Section: Safety Of Aspirin In Otolaryngologic Surgerymentioning
confidence: 99%